(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: The Internet is one of the information technology where the internet is a very fun vehicle to learn and play. The phenomenon that occurs in senior high school (SMA) Negeri 1 Manado students who on average always use the internet either at home or internet cafes (Warnet) in allegedly using the internet and accessing information without being filtered whether it can be consumption for use by students such as sensual images or everything something that does not need to be known as a student, so it is suspected to have a positive or negative impact for students In this study researchers used a qualitative approach with Descriptive method. Descriptive method is used to describe the situation and events under study by describing and exposing objects at the same time based on facts. the number of samples was 95 students and the sampling technique was a simple Sample and random Strati fi ed technique. The results showed that the importance of Internet messages for users where the messages are current or actual, interesting presentation, and easy to understand messages from the Internet because the language is interesting, brief and clear. The Internet can increase knowledge and then change in behavior in the sense of increasing insight and get more friends both within the country or abroad, further messages via the Internet can be trusted is the science but lack of confidence in the messages from the internet on gossip-gossip celebrities. The advantages or advantages of using the internet is to get news from around the world, then Science and technology and the increase of friends both domestically and abroad. Keywords: Information Technology, Internet